Precision-cut intestinal slices: alternative model for drug transport, metabolism, and toxicology research. (1st February 2016) - Li, Ming; de Graaf, Inge A. M.; Groothuis, Geny M. M.
ABSTRACT: Introduction : The absorption, distribution, metabolism, excretion and toxicity (ADME-tox) processes of drugs are of importance and require preclinical investigation intestine in addition to the liver. Various models have been developed for prediction of ADME-tox in the intestine. In this review, precision-cut intestinal slices (PCIS) are discussed and highlighted as model for ADME-tox studies. Areas covered : This review provides an overview of the applications and an update of the most recent research on PCIS as an ex vivo model to study the transport, metabolism and toxicology of drugs and other xenobiotics. The unique features of PCIS and the differences with other models as well as the translational aspects are also discussed. Expert opinion : PCIS are a simple, fast, and reliable ex vivo model for drug ADME-tox research. Therefore, PCIS are expected to become an indispensable link in the in vitro – ex vivo – in vivo extrapolation, and a bridge in translation of animal data to the human situation. In the future, this model may be helpful to study the effects of interorgan interactions, intestinal bacteria, excipients and drug formulations on the ADME-tox properties of drugs. The optimization of culture medium and the development of a (cryo)preservation technique require more research.